AGEING ‘HERE’ OR ‘THERE’? SPATIOTEMPORALITIES IN OLDER LABOUR MIGRANTS’ RETURN ASPIRATIONS FROM THE AZORES - Sampaio, Dora (2018)
In this article, I seek to unpack the multiple spatiotemporalities in older migrants’ ideas about return, shedding light on the complex set of motivations and imaginaries that precede return migration. The paper springs from a space-time approach based on the assertion that return aspirations are permanently shaped and negotiated both in and out of place. The discussion is framed around 36 in-depth life narrative interviews with later-life labour migrants living in the Azores, and a seven-month period of ethnographic fieldwork. The role of spatial dimensions such as the place of settlement and the country of origin, and temporal features such as age, length of stay in the host country or stage of life at the time of migration, is discussed in detailed. The paper identifies a ‘family-work matrix’ and a ‘home-host country dialectic’ as central forces shaping migrants’ thoughts and possibilities of return. The multi-stranded, time-fluid, space-induced, context-dependent nature of (return) migration decisions is highlighted and it is shown that an apparent satisfactory social integration in the place of settlement does not, by itself, prevent migrants’ desire to return.